Dreams, Shrines and Mystic Sufi in Palestine - Aref Abu-Rabia, (Journal of Basic & Applied Sciences, 2021)
This paper describes common Sufi beliefs regarding dreams and shrines in Palestine during the 20th century. These beliefs developed during joint and private seasonal visits (ziara). Gaining insight into the sociology of the Sufi cult of saints can enrich our understanding of similar cults in other places and shed light on the reasons for their absence in other societies. The research examines the phenomenon of true dreams at saints’ shrines, and explores the historical and contemporary scope of dream pilgrimages to these shrines. Ceremonies that involve visiting saints’ shrines have encouraged socio-cultural and psychological-therapeutic dependence of the pilgrims with regard to these shrines. This dependence relationship is deeply rooted in their collective psyche and reinforced and legitimized through Palestinian folklore. This paper is based on primary and secondary sources, interviews with Sufi and people who have been active in participating in these rituals, as well as archival and documentary material, a review of published and unpublished materials, books, and scientific journals.